Esteban Arias, Roberto Ayala, Giovanni Beluche y Roberto Fragomeno: El neoliberalismo en sus trabajos y sus días - Barrera Rivera, Dan Abner (2024)
Esteban Arias, Roberto Ayala, Giovanni Beluche y Roberto Fragomeno: El neoliberalismo en sus trabajos y sus días